2023
DOI: 10.3390/polym15040985
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stacking Sequence on Mechanical Properties of Basalt/Ramie Biodegradable Hybrid Polymer Composites

Abstract: In this study, the mechanical properties of basalt/ramie/polyester hybrid composite laminates were investigated. A matrix of 45% polyester was used, as it has good bonding properties between fibers. The composite laminates were fabricated using a hand layup technique, with seven layers stacked in different sequences and impregnated in the polyester matrix to create a hybrid configuration. Tensile, flexural, impact, compression, and hardness tests were conducted according to ASTM standards for mechanical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…JBBJ samples have higher strength because they contain strong jute fibers that effectively absorb energy and maintain strong interfacial bonding with the matrix. The obtained results are consistent with those of Ramesh et al [20] regarding Basalt and Ramie composites, indicating similar impact responses, as well as the observations made by Venkateshwaran et al [33] in their study on Jute/Banana epoxy composites, where Banana fiber exhibited lower impact strength than Jute fiber. Furthermore, De Rosa et al [13] discovered that the exterior layers of laminates are the most damaged during failure, and reinforcing these layers with high-strength fibers enhances impact strength [17].…”
Section: Impact Strengthsupporting
confidence: 91%
See 1 more Smart Citation
“…JBBJ samples have higher strength because they contain strong jute fibers that effectively absorb energy and maintain strong interfacial bonding with the matrix. The obtained results are consistent with those of Ramesh et al [20] regarding Basalt and Ramie composites, indicating similar impact responses, as well as the observations made by Venkateshwaran et al [33] in their study on Jute/Banana epoxy composites, where Banana fiber exhibited lower impact strength than Jute fiber. Furthermore, De Rosa et al [13] discovered that the exterior layers of laminates are the most damaged during failure, and reinforcing these layers with high-strength fibers enhances impact strength [17].…”
Section: Impact Strengthsupporting
confidence: 91%
“…The study found that glass fiber mats as skin layers and core significantly impacted composites' mechanical properties. Velumayil et al [20] studied the mechanical properties of basalt (B) and ramie (R) polyester hybrid composite laminates. Seven layers were built in different orders and impregnated into the polyester matrix to create hybrid fibre laminates.…”
Section: Introductionmentioning
confidence: 99%
“…(Hamada et al 2023) suggested that solid wastes are suitable alternative for binder/aggregates in ultra-high-performance concrete, however improvement techniques should be proposed with suitable design and testing methods. Few studies were proposed with the use of fibres and eco-friendly materials in the development of composites to investigate the mechanical properties (Karthik et al 2022, Fayaz et al 2022, Murali et al 2023, Ramesh et al 2023a, Ramesh et al 2023b, Ahmed et al 2017. Similar studies were performed with the RA as a replacement to aggregate in the concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Every pod carries up to 10 seeds, and while it is fully mature, the pod bursts open explosively, dispersing its seeds up to 20 m from the tree (Karthik et al 2023) Despite having exceptional energy and hardness, artificial fibre reinforced composites are costly and not biodegradable. Herbal fibres are becoming extra popular because to their accessibility, acceptable precise energy and modulus (Ramesh et al 2023) light weight, low price, and biodegradability (Baley 2022). Moreover, in comparison to composites made from natural fibres, synthetic fibres like carbon fibres and glass fibres pose extra environmental and fitness dangers to the human beings worried within the production in their associated composites (Jawaid et al 2011).…”
Section: Introductionmentioning
confidence: 99%